Multiple urethral calculus misdiagnosed as urethral stricture: The role of imaging in unknotting the confusion - Danfulani, M.; Saidu, S.A.; Musa, M.A. (Asian Journal of Medical Sciences, 2016)
Urinary Tract Calculi Impaction / finding in the male urethra is extremely uncommon and can usually be secondary to upper urinary tract calculus formation or primarily arising from the urethra either due to stricture or post-trauma. There is paucity of urethral stricture report in Nigeria, thus this case is reported to highlight the role of imaging in the prompt diagnosis and management of urethral diseases; and to advise urologists to at least always request for imaging modality in their routine evaluation of urethral pathologies. We report a case of a 55 years old male farmer who presented in the Accident and Emergency Unit of our facility with signs and symptoms of acute urinary retention. A working diagnosis of urethral stricture was entertained and prompt diagnosis was made on image. Existing literatures outlining the pathologies, clinical presentation, therapeutic consideration and imaging as it relates to urethral calculi were reviewed. We thus concluded that imaging is very vital and fundamental in order to correctly assess any form of urethral pathology. Asian Journal of Medical Sciences Vol. 7(3) 2016 118-120